The effect of power outages and cheap talk on willingness to pay to reduce outages - Fredrik Carlsson; Peter Martinsson; Alpaslan Akay (Institute for the Study of Labor (IZA), 2009)
Using an open-ended contingent valuation survey, we analyze how (i) experience of a power outage due to one of the worst storms ever to hit Sweden and (ii) a cheap talk script affect respondents' WTP to avoid power outages. Experience significantly increases and a cheap talk script decreases the proportion of respondents with zero WTP. There is no significant effect in either case on stated WTP conditional on a positive WTP. The paper concludes with a discussion on the use of valuation studies shortly after the occurrence of an undesirable event.
urn:nbn:de:101:1-20090825460
Keywords: C25; D12; Q41; 330; Contingent valuation; cheap talk; experience; power outages; Elektrizitätswirtschaft; Betriebliche Störung; Willingness to pay; Informationsverhalten; Kommunikation; Schweden